The Position of Hindu-Balinese Women in Inheritance Law Pluralism: A Study of Supreme Court Decision Number 2824 K/PDT/2017 - Dana Paramitha, Luh Gede; Atu Dewi, Anak Agung Istri Ari (Westscience Press, 2025)
This article examines the position of Hindu-Balinese women in the context of pluralistic inheritance law in Indonesia, particularly from the perspective of the Civil Code and Balinese customary law. Through a study of Supreme Court Decision Number 2824 K/Pdt/2017, this article examines the extent to which the formal legal system provides protection for women's inheritance rights. The analysis shows that the Civil Code guarantees equality of inheritance rights without distinction of gender, while Balinese customary law still prioritizes the line of inheritance. Although the 2010 MUDP Decision has accommodated women's rights, the Supreme Court in its decision did not substantially acknowledge this development, thus demonstrating the weak support for gender justice in national legal pluralism.